2015
DOI: 10.1038/srep09991
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from alcohol-treated hepatocytes horizontally transfer liver specific miRNA-122 and sensitize monocytes to LPS

Abstract: Hepatocyte damage and inflammation in monocytes/macrophages are central to the pathogenesis of alcoholic hepatitis (AH). MicroRNAs (miRNAs) regulate all of these processes. MiRNA-122 is abundantly expressed in hepatocytes while monocytes/macrophages have low levels. The role of exosomes in AH and possible cross talk between hepatocyte-derived exosomes and immune cells is not explored yet. Here, we show that the number of exosomes significantly increases in the sera of healthy individuals after alcohol binge dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
315
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(351 citation statements)
references
References 51 publications
17
315
1
2
Order By: Relevance
“…Indeed, we showed that, unlike EVN, EVF do not suppress proliferation or expression of fibrosis- or activation-related genes in HSC. Since inflammatory pathways in the liver have been linked to EV communication between hepatocytes and monocytes [65], an interesting area for future study will be to determine whether the therapeutic actions of EVN in fibrosis are in part attributable to the action of EV miRs and/or other EV constituents on pro-inflammatory gene expression and regulation of inflammatory cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we showed that, unlike EVN, EVF do not suppress proliferation or expression of fibrosis- or activation-related genes in HSC. Since inflammatory pathways in the liver have been linked to EV communication between hepatocytes and monocytes [65], an interesting area for future study will be to determine whether the therapeutic actions of EVN in fibrosis are in part attributable to the action of EV miRs and/or other EV constituents on pro-inflammatory gene expression and regulation of inflammatory cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Following EV-mediated transfer of miRNA122 to monocytes, the monocytes become highly sensitive to LPS, upregulating their secretion of IL-1β and TNF-α compared with that after LPS treatment alone. This EV-mediated sensitization of monocytes could promote a state of chronic, systemic inflammation that further exacerbates the diagnosis phenotype and comorbidities in patients with liver disease (59,60 (44). Thus, tumor-derived EVs can function at multiple levels to facilitate tumor growth and metastasis.…”
Section: Suppression Of Immune Responses By Evsmentioning
confidence: 99%
“…In addition, secreted microRNAs can silence their target genes in remote tissues, thereby playing a role in cell-to-cell communication 28,29 .…”
Section: Tnfα and Lps Enhance Secretion Of Mir-122mentioning
confidence: 99%